Joining Forces: Collaborating Internationally to Deliver High-Quality, Online Postgraduate Education in Pain Management. (2011) - Devonshire, Elizabeth; Siddall, Philip J
Abstract : The effective management of pain is a complex and costly global issue, requiring a range of innovative educational strategies to enable culturally appropriate and high-quality health care provision. In response to this issue, the Pain Management Research Institute at the University of Sydney (Sydney, Australia) has established several strategic alliances with other overseas universities to deliver online postgraduate education in pain management. The present article discusses the rationale for joining forces, and the approach adopted in creating and maintaining these alliances. It also provides insights into the benefits, challenges and opportunities associated with collaborative educational initiatives of this nature, from institutional, academic and student perspectives.